Maternal Third Delay and Associated Factors among Women Admitted for Emergency Obstetric Care in Public Hospitals in Sidama Regional State, Ethiopia - Esuyawkal Mislu; Ali Seid; Nigus Bililign; Terefe Woyo; Dubale Dulla (Journal of Pregnancy)
Background. Timing to get obstetric care is critical in preventing maternal death and disability. Maternal third delay, the delay in receiving care after reaching health facilities, involves factors related to organization, quality of care, patient referral, and availability of staff and equipment. However, data is limited on maternal third delay and its associated factors at higher health facilities in Ethiopia. Objective. This study is aimed at assessing the magnitude of maternal third delay and associated factors among women admitted for emergency obstetric care in public hospitals in Sidama Regional State, Ethiopia, 2021. Methods. An institution-based cross-sectional study was conducted from September to November 2021. Face-to-face interview with a structured questionnaire and data extraction from medical charts were carried out in selected 542 women (using systematic sampling method). The collected data were coded and entered using EpiData, and bivariable and multivariable logistic regression analyses were done using SPSS version 25. Statistical significances were declared at p value less than 0.05. Results. Maternal third delay was identified among 29.3% (95%CI=25.2−33.5) of the respondents. Additionally, women who arrived with a referral from other health facilities (AOR=0.311, 95%CI=0.181−0.534), well prepared for birth and its complications (AOR=2.418, 95%CI=1.51−3.869), self-employed (AOR=0.223, 95%CI=0.122−0.409), being a government employee (AOR=0.157, 95%CI=0.063−0.396), having ANC follow-up (AOR=2.795, 95%CI=1.318−5.928), and absence of health professional (AOR=4.63, 95%CI=2.857−7.50) were significantly associated with maternal third delay. Conclusion. This study identified that maternal third delay was high, which indicates that women have not received emergency obstetric care in the recommended time range after they arrived at the health facilities.